AQW051, a novel, potent and selective α7 nicotinic ACh receptor partial agonist: pharmacological characterization and phase I evaluation. (12th January 2015) - Feuerbach, Dominik; Pezous, Nicole; Weiss, Markus; Shakeri‐Nejad, Kasra; Lingenhoehl, Kurt; Hoyer, Daniel; Hurth, Konstanze; Bilbe, Graeme; Pryce, Christopher R; McAllister, Kevin; Chaperon, Frederique; Kucher, Klaus; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Activation of the α7 nicotinic ACh receptor (nACh receptor) is considered an attractive target for the treatment of cognitive impairment associated with neurological disorders. Here we describe the novel α7‐nACh receptor agonist AQW051 as a promising drug candidate for this indication. Experimental Approach AQW051 was functionally characterized in vitro and cognitive effects evaluated in rodent behavioural models. Pharmacokinetics and tolerability were evaluated in three phase I placebo‐controlled studies in 180 healthy subjects. Key Results In vitro, AQW051 bound with high affinity to α7‐nACh receptors and stimulated calcium influx in cells recombinantly expressing the human α7‐nACh receptor. In vivo, AQW051 demonstrated good oral bioavailability and rapid penetration into the rodent brain. AQW051 administered over a broad dose range facilitated learning/memory performance in the object recognition and social recognition test in mice and the water maze model in aged rats. Clinically, AQW051 was well tolerated in healthy young and elderly subjects, with an adverse event (AE) profile comparable with placebo. No serious AEs were reported and all AEs were either mild or moderate in severity at single oral doses up to 200 mg and multiple daily doses up to 75 mg. Once‐daily oral administration of AQW051 resulted in continuous exposure and a two‐ to threefold accumulation compared with steady state was achieved by 1 week. Conclusions and Implications These data support further development of AQW051 as a cognitive‐enhancing agent, as a therapeutic, for example, in Alzheimer's disease or schizophrenia.